The Chief Digital Officer: the roles and tasks of the CDO. - Van Delft, Tjarco (My University, 2019)
A relatively new function has emerged to guide the digital transformation of companies: the Chief Digital Officer (CDO). This thesis clarifies the confusion of the new function and contributes to the academic activity on the CDO by answering the question: how do CDOs perceive their roles and tasks within their organizations, espe-cially compared to those of the CIO? This is done by an extensive review of literature on digital transformation, the roles and tasks of the CIO and the literature available on the CDO which is compared to four case studies in which CDOs were interviewed in-depth. The tasks that the CDO performs are different from the tasks a CIO performs, because the CIO is respon-sible for his IM department in a supportive way to the organization by enforcing the vision and strategy set by other C-level executives and the CDO is responsible for changing the whole organization, including its vision, strategy and all departments to a digital state (in cooperation with other C-level executives). The perception of roles of the CDO are elaborated on by using Mintzberg’s six managerial roles: as an entrepreneur, the CDO creates digital products and changes an organization to a digital state; as a leader, the CDO inspires, facilitates and motives his subordinates to create a mindset that aligns with the digital strategy; as an allocator, the CDO allocates resources to match the digital strategy and objectives; as a liaison, the CDO speaks to people inter-nally to steer the organization toward a digital mindset; as a monitor, the CDO scans the environment for digital opportunities; and as a spokesperson, the CDO informs other departments and executives in the organization about the digital agenda and progress. Companies that want to digitally transform can use this thesis as a guide, clarifying the roles and tasks of the CDO and CIO.